Complementary studies of the Perlidae (Insecta: Plecoptera) fauna from the Paranapiacaba Mountains using DNA barcode data - de Almeida, Lucas Henrique [UNESP]; Duarte, Tácio; da Conceição Bispo, Pitágoras [UNESP] (Magnolia Press, 2024)
The Paranapiacaba Mountains are a region of Brazil where the stonefly fauna is relatively well known. Despite this, there are still gaps in knowledge that need to be filled. In this study, through field sampling and molecular analyses, we have updated the taxonomic knowledge of Perlidae species in this region. Our study employed DNA barcoding methods to complement traditional morphological approaches, facilitating the association and description of the nymphs of Anacroneuria itajaimirim Bispo & Froehlich 2004. Additionally, we generated DNA barcode sequences for Anacroneuria iporanga Bispo & Froehlich 2004. Our results contributed to knowledge about Perlidae from the Paranapiacaba Mountains, highlighting the importance of DNA barcode data in the association of immature stages and species delimitations. Although the stoneflies of Paranapiacaba Mountains have been relatively well-studied, our results reveal that we still have deficits in knowledge of the fauna of this region.
Keywords: aquatic insects; association; freshwater; nymph; stoneflies